Studi di Archeologia del Vicino Oriente Scritti degli allievi fiorentini per Paolo Emilio Pecorella - MAZZONI, Stefania (Studi e saggi, 2012)
The book presents recent studies and research by the students of Paolo Emilio Pecorella, a lecturer in Archaeology and Art History of the Ancient Near East at the University of Florence. The contributions reflect the numerous interests and activities in the field promoted by Pecorella and continued now by his school: in Syria and Mesopotamia (J.S. Baldi, S. Nannucci, V. Orsi, C. Coppini and G. Baccelli), in Anatolia (F. Manuelli, A. D'Agostino, G. Guarducci and S. Valentini), in Cyprus (L. Bombardieri), and in Iran (S. Anastasio).